Sharks and marine batoids management in Colombia: Policy instruments, management duty and implications for their populations and stakeholders. (November 2022) - Puentes, Vladimir; Mejía-Falla, Paola A.; Ramirez, John G.; Manjarrés-Martínez, Luis M.; Rguez-Baron, Juan M.; Zapata, Luis A.; Tavera, José; Gómez-Delgado, Fabio; Barreto, Carlos G.; Zambrano, Emiliano; Villa, Ángel A.; Navia, Andrés F.
Abstract: Until March 2021, marine Chondrichthyans in Colombia were fishery resources, administered under the Ministry of Agriculture (MinAgricultura) with the fisheries authority had an NPOA Sharks as a guide for their management. After that, and under the Decree 281 of 18 March 2021 issued by the Ministry of Environment of Colombia, a new policy (called the Environmental Plan for the protection and conservation of sharks, marine rays, and chimaeras of Colombia)emerged, and the management duty of Chondrichthyans changed from a fishery resource to a hydrobiological resource, thereby prohibiting commercial use of those species and transferring its management to the government's environmental sector. This paper discusses the two policy instruments created for the same group of fishes, the consequences of changing the government management duty from one sector to another by the new policy created, and the implications for the environmental, fisheries, control, and surveillance sectors, civil organizations, and even for sharks. In addition, a logical framework analysis method was carried out to identify shark vulnerability and stakeholders, and to analyze both policy instruments and their positive and negative outputs. Part of the environmental sector celebrated the issued decree as an unprecedented achievement for Colombia. In contrast, other stakeholders, including the fisheries sector, declared that the ban on sharks/batoids for trade and fishing indirectly affects marine fisheries and fishers since these species are commonly bycatch in most of them. Consequently, shark/batoid bycatch management was raised as the central management issue since fishing activity is the main threat for elasmobranchs. Alternatives are proposed for conservation and fisheries to coexist, obtaining mutual benefits, avoiding confrontation, and heading towards sustainable development from different perspectives. Highlights: Sharks/batoids are vulnerable to fishing and other pressures due to life-history traits. Shark/batoids are bycatch in most Colombian marine fishing gear/methods at all scales. Governmental conservation decree of 2021 establishes sharks/batoids protection/conservation measures in Colombia. A comparison of two policy instruments was carried out. Government and civil society implications raised regarding recent sharks/batoids conservation measures.